Enhancing diabetic elderly health diet education through mobile application: an interdisciplinary conceptual framework - Jinglong, Li; Che Me, Rosalam; Ahmad, Faisul Arif; Qisen, Zhu (Wise Academia Research Solutions Malaysia, 2024)
The increasing incidence of diabetes among the elderly has heightened the demand for effective healthcare solutions, with mobile applications emerging as promising options for managing healthy diet education. However, age-related declines in cognitive, physical, and sensory functions may reduce elderly's willingness to learn new technologies. This study aims to examine the dietary needs of diabetic elderly, identify factors influencing their learning habits, and explore key elements in designing and accepting mobile applications. Using a four-step approach—identifying target users, reviewing literature, pinpointing key variables, and developing a conceptual framework—the study found that exercise, BMI, and a healthy diet attitude significantly shape dietary habits. It also identified appearance, functionality, and interface design as critical factors for mobile applications. Additionally, perceived ease of use, usefulness, safety, and enjoyment were found to be important for acceptance. These elements should guide future research in designing mobile applications for diabetic elderly healthy diet education